Teacher and second grade student’s perspective towards interaction in EFL classroom - Widyasri, Windy; Br. Kembaren, Farida Repelita Waty; Daulay, Sholihatul Hamidah ((JELE) Journal Of English Language and Education, 2023)
The purpose of this article was to analyze the pattern of interaction in the EFL learning classroom. Observation, field notes, transcription, and a semi-structured interview were used to collect data. One teacher and thirty students participated in this study to analyze the typical interaction that they have in the classroom and the cause for that interaction. The study's findings were presented in the form of a description and interpretations of the interaction. The results showed that both teacher and learners admitted that they have interaction between students and teacher and also students and other students. Teacher and students realize that interaction in the EFL classroom is important, however the reason behind the interaction is various. The interview shows that the interaction that initiated by teacher are lecturing, checking the students, understanding, grabbing students attention, checking the students attendance, giving praises or encourages, asking questions and opinion, giving direction, reminding material. The kind of interaction that students do are discussing the material, asking and answering questions, and silent or body movements